The Role of FOMO on Netflix Subscription Intention - Damayanti, Fenny; Hurriyati, Ratih; Disman, Disman; Hendrayati, Heny; Pamuji Aminullah, Zakariya (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study examines the influence of Fear of Missing Out (FOMO) on Generation Z university students' Netflix subscription intention. The research is motivated by the increasing reliance of students on streaming platforms for entertainment, cultural exposure, and informal learning, alongside heightened psychological pressures associated with digital connectivity. Method: A quantitative explanatory approach was employed using online questionnaires distributed to 385 university students aged 18–24 who actively use Netflix. Out of 400 questionnaires distributed, 385 were returned and deemed valid (response rate: 96.25%). Non-probability purposive sampling was applied. Data analysis included descriptive statistics, reliability and validity testing (HTMT criterion for discriminant validity), and hypothesis testing using Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping. Results: Students exhibited moderate-to-high FOMO levels (M = 3.87, SD = 0.92) and predominantly high subscription intentions (M = 4.12, SD = 0.78) on a 5-point Likert scale. FOMO had a significant positive effect on subscription intention (β = 0.432, p < 0.001), explaining 43.2% of the variance. Perceived usefulness, social influence, and digital literacy were measured as contextual variables but not incorporated into the structural model. The remaining 56.8% of unexplained variance indicates that other psychological, social, and technological factors warrant future investigation. Novelty: This study provides empirical evidence that FOMO is a significant predictor of streaming platform adoption among Generation Z. The findings offer practical implications for platform providers and educational institutions to develop targeted interventions addressing psychological drivers and digital literacy competencies relevant to subscription behavior in higher education contexts.